O curso online de proficiência em língua inglesa da Universidade Franciscana (UFN): um estudo à luz da análise crítica de gênero - Buzetto, Bruno Souza (2023)
Universidade Franciscana (UFN) is a private higher education institution in Santa Maria (RS) that has been offering English language proficiency tests to its students and to the academic community for over 15 years. Due to the social distancing caused by the COVID-19 pandemic in 2020, the testing process was remodeled into an online course format that lasts two and a half weeks, with different activities as assessment tools. Because it is a relatively new testing format in the institution, no studies have yet been conducted on this online proficiency course. In this sense, this master’s thesis aims to analyze the UFN's online English proficiency course from its contextual and textual elements in the light of the theoretical assumptions of Critical Genre Analysis (CGA) (MOTTA-ROTH, 2006; 2008a; 2008b) in order to identify the characteristics of this social practice and the linguistic knowledge required from the examinees to obtain certification. First, the discourse community (SWALES, 1990) of the course was described and the processes related to this discourse practice (FAIRCLOUGH, 1989; 1995; 2010) were identified and described. Then, the source texts were identified and described in relation to its genre and authenticity; finally, the questions present in the tests administered throughout the 9 online courses in the corpus were analyzed in relation to quantity, structure, types (FUZER et al., 2017), foci (MARCUZZO and RADÜNZ, 2019) and strata of language mobilized (HENDGES, 2005; MOTTA-ROTH, 2008a; RADÜNZ, 2020). The results point out that the UFN online English proficiency course is embedded in a discourse community that encompasses many processes and several people capable of teaching the knowledge about shared goals and purposes of the course to new members. Moreover, the course presents source texts that, for the most part, instantiate genres of the academic and journalistic spheres, being the abstract and the science popularization news the most recurrent ones. The questions of the course activities are mainly of the "correct alternative" type (49%) and focus mainly on textual evidence (31%), although some questions also focus on more abstract aspects of language, such as genre and ideology. Also, the course mobilizes different strata of language in its questions, emphasizing the Semantics and Pragmatics strata (60%). Finally, we can say that the UFN testing process demands from the examinees the ability to read and understand texts based on questions that involve both concrete and abstract aspects of the language.